A Local Housing Strategy in Inner City Perth - Greive, S.; McKenzie, Fiona Haslam (Australian Sustainable Cities Network, 2009)
This research describes a Perth inner city local government authority's attempts to instigate a housing strategy with particular focus on the provision of affordable housing. Although the study centred on the current and future needs of the Town's residents the research team also considered the broader context in terms of housing market dynamics, the impact of government policy and the operations of allied housing support agencies and community organisations. We report on the experience of working directly with a local government authority to develop an affordable housing strategy. This experience highlights a range of practical responses. It also serves to detail the layers of inhibitors that were revealed during the process. These include the lack of housing knowledge and experience within the planning profession; the need to modify established work practices and policies; and council's reluctance to further overburden its budgets and staffing levels. These inhibitors all conspire to undermine the potential effectiveness of local housing strategies to deliver necessary housing reforms. The overall findings suggest that although local housing strategies can be effective vehicles for fostering housing reforms it is going to require a lot more concerted attention and cooperation between higher levels of government to enable and resource the process.